Problems of planning foreign language lessons (Eurasian Journal of Learning and Academic Teaching, 2024)
This article touches on some problems of planning a foreign language lesson, issues of preparation for a foreign language lesson based on a modern model of didactic analysis, which makes it possible to make thorough, methodologically sound decisions on planning a foreign language lesson.